Management of Education Training And Supervision Leadership In Improving The Performance of Regional Structural Officials - Chaeroni, Nanang; Kartika, Ikka; Iriantara, Yosal; Fachrurozi, H. Fachrurozi (The International Journal of Education Management and Sociology, 2023)
The purpose of this study is to determine the planning, organizing, assessment, and constraints that exist in educational and training institutions at the Center for Human Resource Development. This research method uses a qualitative approach with data collection techniques through observation, interviews, and documentation studies. Research results show: (1). Plans are made to arrange activities in the implementation in detail and detail. (2.) Organization forms a structure to foster and guide in providing instructions, and directions in analyzing and solving problems in each assignment that has been given (3). The implementation motivates the trainees to work on the programs that have been prepared, namely to improve the performance of officials so that it benefits them (4). Assessment of education and training participants that have been carried out on training participants is a stage for measuring the ability to make decisions (5). Obstacles that exist in improving the performance of officials through changes and innovations in public services are already underway and can be overcome the obstacles encountered.